Ekstraksi Karakter Citra Menggunakan Optical Character Recognition Untuk Pencetakan Nomor Kendaraan Pada Struk Parkir - Khairi Ibnutama; Muhammad Gilang Suryanata (STMIK Budi Darma, 2020)
Security in public parking facilities can be increased by adding the vehicle plate number to the parking receipt. This aims to prevent misidentification when the vehicle exits the parking facility due to negligence of the vehicle owner or the purpose of an irresponsible party. The license plate number can be printed on the parking receipt by extracting the characters from the vehicle image which is generally acquired at the parking entrance portal. The character extraction process can be done using the Optical Character Recognition method using the Tesseract library. Tesseract is the most accurate Optical Character Recognition library in its recognition, so that the extraction process can produce vehicle license plate text with minimal errors.